The Influence of Emotion Regulation and Social Intelligence on Empathy in Young Adults - Winda Kristina; Asy Sifa Safarina; Unzurna Unzurna; Yulina Eva Riany (Jurnal Psikologi Teori dan Terapan, 2026)
Background: The massive digital environment challenges empathy development due to reduced face-to-face interactions and nonverbal cues. Objective: This study aims to analyze the influence of emotion regulation and social intelligence on empathy in young adults and to examine the potential mediating role of social intelligence. Method: Using a quantitative cross-sectional design, data were collected from 341 Indonesian young adults using the DERS-SF, TSIS, and IRI scales. Data analysis was performed using multiple linear regression and path analysis with bootstrapping. Result: Simultaneous test results showed that emotion regulation and social intelligence significantly influence empathy (F = 18.452, p < 0.001), although their effective contribution was 9,8%. Social intelligence (t = 6.075, p < 0.001) and emotion regulation (t = 2.351, p = 0.019) were significant predictors of empathy. Conclusion: These findings confirm that effective emotional management and socio-cognitive skills are key developmental tasks for young adults. The low R-square value (9,8%) indicates that emotion regulation and social intelligence explain a small proportion of empathy's variance, while the remaining 90.2% being attributable to other external factors. Abstrak Latar Belakang: Lingkungan digital yang masif menghadirkan tantangan bagi perkembangan empati akibat berkurangnya interaksi tatap muka dan isyarat nonverbal. Tujuan: Penelitian ini bertujuan untuk menganalisis pengaruh regulasi emosi dan kecerdasan sosial terhadap empati pada usia dewasa muda serta menguji potensi peran mediasi kecerdasan sosial. Metode: Menggunakan desain kuantitatif cross-sectional, data dikumpulkan dari 341 dewasa muda Indonesia menggunakan skala DERS-SF, TSIS, dan IRI. Hasil: Analisis data dilakukan dengan regresi linier berganda dan path analysis dengan bootstrapping. Hasil uji simultan menunjukkan bahwa regulasi emosi dan kecerdasan sosial secara signifikan mempengaruhi empati (F = 18,452, p < 0,001), meskipun kontribusi efektif total sebesar 9,8%. Baik kecerdasan sosial (t = 6,075, p < 0,001) maupun regulasi emosi (t = 2,351, p = 0,019) merupakan prediktor empati yang signifikan. Kesimpulan: Temuan ini menegaskan bahwa manajemen emosi yang efektif dan keterampilan sosio-kognitif penting untuk tugas perkembangan kunci bagi dewasa muda Indonesia. Nilai R-square yang sangat rendah (9,8%) secara eksplisit menunjukkan bahwa regulasi emosi dan kecerdasan sosial hanya menjelaskan sebagian kecil varians empati, dengan sebagian besar (90,2%) disebabkan oleh faktor eksternal lainnya.